CHALLENGES IN TEACHING FOREIGN LANGUAGES IN NON-PHILOLOGICAL UNIVERSITIES (European Science Methodical Journal, 2024)
Teaching foreign languages in non-philological universities presents unique challenges due to the specialized nature of these institutions, where foreign language courses are often not the primary focus of academic curricula. Students in fields such as engineering, medicine, and business may perceive language learning as non-essential, leading to low motivation and limited engagement. Additionally, foreign language courses in non-philological universities typically receive limited time, making it difficult to achieve proficiency. Other challenges include varying student proficiency levels, inadequate resources, lack of specialized teacher training, and the struggle to integrate cultural context with language learning. Despite these obstacles, potential solutions such as curriculum integration, differentiated instruction, use of digital resources, and incorporating industry-specific language training can enhance the effectiveness of foreign language teaching. This article explores these challenges in depth and offers practical recommendations to improve foreign language education in non-philological settings, ensuring that students develop language skills that are valuable in a globalized world.